2007
DOI: 10.1371/journal.pone.0001260
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Infected Children Living in Central Africa Have Low Persistence of Antibodies to Vaccines Used in the Expanded Program on Immunization

Abstract: BackgroundThe Expanded Program on Immunization (EPI) is the most cost-effective measures to control vaccine-preventable diseases. Currently, the EPI schedule is similar for HIV-infected children; the introduction of antiretroviral therapy (ART) should considerably prolong their life expectancy.Methods and Principal FindingsTo evaluate the persistence of antibodies to the EPI vaccines in HIV-infected and HIV-exposed uninfected children who previously received these vaccines in routine clinical practice, we cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 36 publications
4
35
1
1
Order By: Relevance
“…Low responsiveness to measles vaccine in HIV-infected children has been associated with nutritional status rather than with HIV infection (33). This cannot be applied to our findings for the HEU infants concerning hepatitis B and DTP vaccines, as there were no children with a poor general health status in our study.…”
Section: Discussioncontrasting
confidence: 56%
“…Low responsiveness to measles vaccine in HIV-infected children has been associated with nutritional status rather than with HIV infection (33). This cannot be applied to our findings for the HEU infants concerning hepatitis B and DTP vaccines, as there were no children with a poor general health status in our study.…”
Section: Discussioncontrasting
confidence: 56%
“…The study was conducted in accordance with the Declaration of Helsinki. The detailed study design has been reported previously (21). Briefly, children were included in the study if they had received at least a primary vaccine series of three doses of the DTwP vaccine, as certified by their immunization card.…”
Section: Methodsmentioning
confidence: 99%
“…20,21 The HIV infection is also considered to be an important factor contributing to primary and secondary measles vaccine failure. 22,23 Thus, there is a need to characterize the local epidemiology of measles in regions with a growing HIV prevalence, to design new control strategies to protect children before the age of vaccination, and to overcome vaccine failure. 12 Monitoring for measles in Mozambique is conducted through a hospital-based Weekly Information Bulletin System (Boletim Epidemiológico Semanal -BES) notification from health facilities.…”
Section: Introductionmentioning
confidence: 99%